E-business and E-Commerce in the Digital Economy - Misratillaev Sherbek Azamat o’g’li (Scholars Digest Publishing, 2023)
In this article, e-business and e-commerce in the digital economy, i.e. the Internet, bring several new and improved ways to the development of business efficiency. Now we can easily carry out various trades and businesses that were previously impossible or very complicated. Basically, the history of electronic business goes back to the beginning of the revolution in the field of information technologies in the 60s and 70s of the 20th century. The rapid development of information and communication technologies (ICT) has made it possible to simplify and reduce the cost of information exchange between and within enterprises. Further development of e-business cannot be imagined without the use of computer networks. Accordingly, at the beginning of the 60s, experts began to think that it would be possible to establish a global computer connection between people to provide instant access to programs and data, databases from anywhere in the world.
Keywords: Internet, economy, digital economy, electronic business, digitalization, electronic commerce.